Intimate partner violence is independently associated with poor utilization of antenatal care in Arba Minch town, southern Ethiopia: A cross-sectional study. - Dagne Deresa Dinagde; Kassahun Fikadu Tesema; Fitsum Wolde; Gudisa Weyessa Heyi; Gizu Tola Feyisa; Agmasie Damtew Walle (Public Library of Science (PLoS), 2024)
To ensure the best possible health conditions for both mother and fetus throughout pregnancy, skilled healthcare professionals provide antenatal care (ANC) to expectant mothers. Even though the introduction of antenatal care has reduced maternal mortality by 34% since 2002, some atypical behaviors, such as intimate partner violence, have had a significant impact on how often women seek out expert medical treatment during pregnancy. Hence, early identification of such risk factors is very important to decrease maternal mortality from preventable causes. To assess the prevalence and factors of intimate partner violence and associated factors among pregnant women at Arba Minch town, southern Ethiopia. An institution-based cross-sectional study was conducted among 403 mothers who were enrolled from December 1, 2022, to January 30, 2023. The total sample size was allocated proportionately to the number of women attending antenatal care at each public health facility. Thus, systematic sampling was applied. Kobo Toolbox was used for data collection and cleaning, which was then analyzed using IBM SPSS Version 26. Statistical significance was determined at a p-value of less than 0.05. In this study area, the prevalence of intimate partner violence among pregnant women was 35% (95% CI: 30.5-39). The associated factors of intimate partner violence were late initiation of antenatal care (AOR = 3.81, 95% CI: 1.7, 6.04), non-autonomous women (AOR = 1.8, 95% CI: 1.18, 3.14), inadequate antenatal utilization (AOR = 3.41, 95% CI: 1.8, 6.2), and a husband with an extra wife (AOR = 6.0, 95% CI: 4.2, 10.57).This study showed that more than one-third of pregnant women in this study area were facing intimate partner violence. Having extra wife, lack of women's autonomy, less antenatal care utilization and late initiation of antenatal care were associated with Intimate Partner Violence (IPV). Therefore, it is essential to greatly empower women and provide them significant prestige in the home.